2011
DOI: 10.1007/s10511-011-9205-6
|View full text |Cite
|
Sign up to set email alerts
|

Solution of linear radiative transport problems in plane-parallel atmospheres. I.

Abstract: A new method for determining various quantities describing the radiation field in an inhomogeneous, plane-parallel atmosphere is proposed in this two-part paper. The essence of this method is the reduction of the boundary value problems which arise during the customary statement of various astrophysical problems associated with solving the radiative transfer equations to initial value problems. Compared to previous attempts in this area, the proposed method is universal and simple. The first part of this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the mentioned fundamental works (Nikoghossian, 2011(Nikoghossian, , 2014 we have obtained the representations of composition groups in the form of second order supermatrices, which establish the adding law for global optical properties (reflection and transmittance coefficients) of scattering and absorbing media when being they combined. It was also shown that these representations also describe the transition from one optical depth to the another, which, in determining the field of radiation inside the medium, can be considered as a law of translation between different depths.…”
Section: The Symmetry Properties Of Basic Super-matricesmentioning
confidence: 99%
“…In the mentioned fundamental works (Nikoghossian, 2011(Nikoghossian, , 2014 we have obtained the representations of composition groups in the form of second order supermatrices, which establish the adding law for global optical properties (reflection and transmittance coefficients) of scattering and absorbing media when being they combined. It was also shown that these representations also describe the transition from one optical depth to the another, which, in determining the field of radiation inside the medium, can be considered as a law of translation between different depths.…”
Section: The Symmetry Properties Of Basic Super-matricesmentioning
confidence: 99%